Antidiabetic Potential and Antioxidant Activity of Olea europaea subsp. Cuspidata (Indian Olive) Seed Extracts. (30th September 2022) - Akhtar, Muhammad Furqan; Ashraf, Komal Maria; Saleem, Ammara; Sharif, Ali; Zubair, Hafiz Muhammad; Anwar, Fareeha
Abstract : The aim of the present study was to evaluate the antioxidant and antidiabetic potential of Indian olive seed extracts. Plant seeds were sequentially extracted with n-hexane, chloroform, methanol, and water. 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) scavenging and alpha-amylase inhibitory activities of extracts were carried out. Olea europaea methanolic extract (MEOE) and aqueous extract (AEOE) were orally administered to normoglycemic and alloxan-treated diabetic rats so as to determine their hypoglycemic effect. High-performance liquid chromatography (HPLC) analysis showed gallic acid, ferulic acid, quercetin, and vanillic acid in MEOE. It was found that the methanolic and aqueous extracts exhibited the maximum DPPH and alpha-amylase inhibition activities, respectively. MEOE and AEOE exerted a significant decline in the fasting blood sugar in diabetic animals (p < 0.05 ); however, they did not cause hypoglycemia in nondiabetic animals. Treatment with MEOE and AEOE reduced the aggravated liver and kidney function biomarkers. Aggravated levels of oxidative stress biomarkers including superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH), and malondialdehyde (MDA) were restored by treatment with MEOE. Moreover, MEOE improved the count of islets of Langerhans in the pancreas, fatty changes, and enlarged sinusoidal spaces in the liver and necrosis of the glomerulus and tubular cells of the kidney in diabetic rats. This study showed that the African olive seed extract effectively managed experimental diabetes and restored the normal functions and histology of the liver and kidney in diabetic rats through the reduction of oxidative stress.